Influence of Variety and Cultivation Technologies on Cucumber Growth, Yield and Insect Pests Management in Sierra Leone - , Alusaine Edward Samura; , Willam Flomo; , Vandi Amara; , Dan David Quee; , Vandi Ibrahim Kallon (Archives of Current Research International, 2025)
The present study aimed to evaluate the influence of different cultivation technologies on the insect population, damage, weeds population and damage growth and yield of cucumber in two cropping years. Cucumber is an important and versatile fruit and vegetable because of its various uses, ranging from salads, pickles, and beauty in Sierra Leone. However, the cultivation of this crop is hindered by pests diseases and poor soil fertility. A two-year field experiment was conducted at the School of Agriculture and Food Science to evaluate the effect of cultivation technologies on the management of pests and weeds cucumbers. The experiment was laid in two two-factor completely randomized design (FCRD) with three replications. The results revealed that cultivation technology one (CT1) had a positive impact and recorded the highest growth and yield during the evaluations (6.5 and 7.8 t/ha). The results on pest and weed management revealed that cultivation technology three (CT3) proved to be the most potent in insect pest management, while cultivation technology two (CT2) was effective in weed management. The economic analysis showed that cultivation technology one (CT1) generated the highest revenue for both 2023 (Le 1,950.00) and 2024 (Le 2,340.00) evaluation years. The study concluded that there are potential benefits of using cultivation technology one and two and recommended that cultivation technology one and two (CT1 and CT2) should be adopted by farmers in the cultivation of cucumbers.